FORMULASI PEMBUATAN MEDIA TANAM BERBASIS LIMBAH KELAPA SAWIT SEBAGAI MEDIA TANAMAN HIAS (Aglonema) - Pradifta, Ika Ucha; Effendi, Zulham; Syukri, Muhammad; Sukrinda Harahap, Marisa (Agro Estate, 2023)
The increase in waste from palm oil processing in Indonesia has a very bad effect on the environment and society. In recent years ornamental plants are very popular in every community, they can help the oil palm industry in reducing the increase in waste by turning it into organic fertilizer. The aims of this study were to determine the content of N,P,K, C-organic, C/N produced from organic fertilizer mixed with empty fruit bunches (tankos) with LCPKS and to determine the effect of application of tankos compost fertilizer. on ornamental plants aglonema flowers. This research was carried out using the RAK method with two factors. The first factor is the use of the number of tankos (J). The second factor is the use of the amount of liquid waste (A). Each treatment combination was repeated 3 times. The data was processed using statistics with analysis of variance (ANOVA) test with DMRT further test at 5% level. The results of this study showed that the nutrient values of Nitrogen (N), Phosphorus (P), Potassium (K), C-organic, and C/N were very significant in each treatment. The effect of applying compost to aglonema flower plants was not significantly different.